Socioeconomic differences in road traffic injuries during childhood and youth: a closer look at different kinds of road user - Hasselberg, M (BMJ Group, 2001)
STUDY OBJECTIVE—To investigate if there are socioeconomic differences in road traffic injuries among Swedish children and adolescents, and if this applies to the same extent to all categories of road users. To assess the modification effect of gender of child. DESIGN—A closed population-based cohort study based on the Swedish Population and Housing Census of 1985. Individual census records are linked to Sweden's National Hospital Discharge Register (1987-1994). SETTING AND SUBJECTS—All children aged 0-15 years in 1985 (approximately 1.5 million subjects) were monitored for five categories of road traffic injuries over eight years, and divided into seven socioeconomic groups on the basis of parental socioeconomic status. Odds ratios and population attributable risks were computed using the children of intermediate and high level salaried employees as reference group. MAIN RESULTS—The injury risks of pedestrians and bicyclists are 20% to 30% higher among the children of manual workers than those of intermediate and high level salaried employees. Socioeconomic differences are greatest for injuries involving motorised vehicles—that is, moped, motorcycle and car. If all children had the same rate as children in the reference group, the rate for all groups would be 25% lower for moped riders and 37% lower for car drivers. CONCLUSIONS—Socioeconomic differences in road traffic injuries are substantial for both boys and girls. Socioeconomic injury-risk differentials increase when young people use motorised vehicles.   Keywords: traffic exposure; injury; health inequality